Sobre os que não tem jeito: racismo institucional e a identificação do adolescente suspeito a partir da atuação da polícia na cidade do Recife. - Sobral Neto, Maurilo Miranda (2017)
In the present dissertation, we intend to analyze the procedure used by the police to identify the suspect teenager in the city of Recife. When we try to understand the procedure of suspicion, what is noteworthy is the racial issue. Indeed, whilst racism assumes founding conditions in our society, the racial issue emerges as a negative and strategic definer within social control strategies carried out by the police. The hypothesis we draw is that race not only attracts the looks of surveillance on behalf of police agents, but also seems to legitimize, both institutionally and socially, the violent behavior of the police towards the teenagers’ bodies, and against whoever else is affected by the “looks” of suspicion. In addition, we observe that, over the years, race has become a crucial component of the “dangerous individual” social type, and of social groups that represent a threat to the physical and patrimonial integrity of hegemonic groups. These constructions that are focused on dangerous classes, under the pretext of social order maintenance, remain today as criminal policies in the fight against crime, and are camouflaged in discourses of neutrality and the myth of racial democracy. In this regard, we draw on the theoretical lenses of critical criminology to understand the process of suspicion, focusing on the permanence of criminological speeches in the Brazilian context. Finally, still integrating our theoretical framework, we felt the need to handle the analytical instruments proposed by Michel Misse’s concept of criminal suspicion, so as to understand how autonomized is the procedure of suspicion led by the police,a procedure that legitimizes a number of authoritarian interventions and that stems from a set of instruments driven to contain the dangerous character and the deviation that supposedly determine certain individuals. Methodologically speaking, this is an ethnography conducted within the premises of the DPCA – Delegacia da Criança e do Adolescente (the police station specialized in crimes committed by teenagers) through participant observation in which it was possible to analyze between the lines of what constitutes a blurred reality in the discourses of neutrality regarding police action. A police station impacted by the daily violence that drains over a contingent formed by young and poor black people.